Kahnawà:ke : factionalism, traditionalism, and nationalism in a Mohawk community - Reid, Gerald F., 1953- (Iroquoians and their world., 2004)
Today Kahnawà:ke ("at the rapids") is a community of approximately seventy-two hundred Mohawks, located on the south shore of the Saint Lawrence River near Montreal. One of the largest Mohawk communities, it is known in the modern era for its activism-a traditionalist, energetic impulse with a long history. Kahnawà:ke examines the development of traditionalism and nationalism in this Kanien'keká:ka (Mohawk) community from 1870 to 1940.